Research on the Technology of a Multifunctional Intelligent Rural Work Machine. Issue 3 (April 2020) - Liu, Jilu; Wang, Chunfang; Tan, Weibing
Abstract: Based on a full study of the agricultural mechanization market, a three-step strategic development plan for the intelligent rural management machine is formulated. The first generation of our products is now on the market. This rural business machine does not require manual driving, but still requires manual remote field remote control. The research of the project is centered on a cruise intelligent rural operation machine with satellite positioning system. This type of intelligent rural work machine equipped with a navigation system uses GPS satellite navigation, so the positioning accuracy can reach 5 cm. Therefore, we only need to set the work area, and then the machine's measurement and control system can automatically plan the work route. We change different agricultural implements, such as: harvesters, tractors, pesticide sprayers, etc. After the navigation system is installed on these agricultural implements, the main agricultural operations such as planting, spraying, and harvesting of farmers can be completed automatically, which saves labor costs and improves operation efficiency. This rural work machine truly realizes the precision and intelligence of work.